Greek Small and Medium Size Enterprises (SMEs) and the Importance of Forming Wide and Competitive Dynamic Multinational Business Alliances - Sdrolias, Labros; Bitzenis, Aristidis; Aspridis, Georgios; Vlachos, Vasileios; Kakkos, Nikolaos; Škodová Parmová, Dagmar; Kazantzi, Vasiliki (The International Relations and European Integration Research Laboratory - University of Macedonia, 2014)
The complexity of the roles and the variety of offers deriving from the SMEs are considered as a fundamental factor of the economic and social development of Greece. Its entry in the EU, in combination with the increasing globalization of the economy, have inevitably resulted in serious effects in the national and international business cycles, imposing huge requirements and challenges to which the greek SMEs should conform and adapt quickly. Studying thoroughly in recent years the wider environment in which the SMEs operate, in addition to their general business behavior, it has been noted that the greek SMEs face serious organizational and managerial problems. As a result of the previous problem, intense phenomena connected to business analgesia rise, due not only to common exogenous and endogenous factors, but mainly to the managers’ inability to accomplish a deep understanding and to apply a number of competitive business strategies with viable and flexible organizational framework and with increased efficiency. Such a perspective, requests organized collaborative alliances that will allow the access of the autonomous Greek SMEs to the abilities, skills and resources of other international contracting parties of analogous size, so that the first can take advantage of the tangible and intangible characteristics of the latter, in order to enhance their competitive dynamic and consequently obtain a constant access to the international markets.
Keywords: Greek SMEs; business alliances; international business environment; systemic approach; cooperation synergies; organizational forms